Attenuation of atherosclerosis by zerumbone in hypercholesterolaemic rabbits - Othman, Hemn Hassan; Hamzah, Hazilawati; Rahman, Heshu Sulaiman; Abu Bakar @ Zakaria, Md Zuki; Mohamed Mustapha, Noordin (2012)
Atherosclerosis is a condition of the arterial wall injury which is prominently driven by inflammatory responses. The objective of this investigation is to evaluate the anti-inflammatory and/or antiproliferative effect of zerumbone (ZER) against early-developed atherosclerotic lesion in the aorta. New Zealand White male rabbits used in the present study were randomly assigned into seven experimental groups, viz; the control (CN) which was fed a standard rabbit pellet diet, a 1% cholesterol diet (CP), 0.4% ZER (Z+CP) for two weeks before day 0 as preventive measure and thereafter with the course of cholesterol-rich diet, 0.8% ZER (Z1+CP), 1.0% ZER (Z2+CP), 20 mg/kg Simvastatin (S+CP) and 0.8% ZER plus 20 mg/kg Simvastatin (S+Z+CP). Experimental groups of Z1+CP to S+Z+CP acted to represent the therapeutic measure of ZER against earlydeveloped atherosclerosis. Tissue samples were collected from the thoracic aorta and aortic arch at 14 weeks post-feeding for morphological studies. The aortic morphology revealed that while endothelial damage and atheromas plague development progressed in the CP group, those receiving ZER has milder lesions. The effect of ZER was found to be in a dose-dependent manner. Our data indicate that dietary intake of ZER significantly averts and decreases early plague formation and development via inhibition of smooth muscle cells proliferation and inflammatory response.